(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The pandemic conditions are very poor all over the world. The Indian economic conditions also affected micro and macro levels. In the recent days, the unemployment issue is being increasing in our country. The urban population in India has been rising rapidly as millions of migrants are moving to urban areas aspiring for higher earnings and better living. The number of the urban poor is also growing and a significant number of these poor find spaces in slums and continue to struggle for better living standards. Improving their conditions appeal to significant efforts from the governments for better policy designs. However, better policy design requires understanding the commonalities and differences across slums within and between cities. This study was conducted on the living conditions of slums in Vellore district. To find characteristics, such as large average household size, poor housing quality, the living near places for the sewer, low female labour market participation and high school enrolment rates among children, to be common across. This study details in Vellore District. To bring out considerable heterogeneity among different groups within slums of each city concerning living standards, like drainages, sanitation, drinking water, medical, literacy rates and consumption pattern, Overall, to find that slums in Vellore District.